2017
DOI: 10.1051/0004-6361/201628693
|View full text |Cite
|
Sign up to set email alerts
|

The 2008 outburst in the young stellar system Z CMa

Abstract: Context. Z CMa is a complex pre-main sequence binary with a current separation of 110 mas, known to consist of an FU Orionis star (SE component) and an embedded Herbig Be star (NW component). Although it represents a well-studied and characterized system, the origin of photometric variabilities, the component properties, and the physical configuration of the system remain mostly unknown. Aims. Immediately when the late-2008 outburst of Z CMa was announced to the community, we initiated a high angular resoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…), we obtain a separation of 114.2 ± 3.1 mas and a position angle of 136.9 ± 1.5 deg, which corresponds to a projected length of about 131 AU. This measurement and others collected in a time span of 26 yr (Koresko et al 1991;Haas et al 1993;Thiebaut et al 1995;Barth et al 1994;Millan-Gabet et al 2002;Bonnefoy et al 2016) are reported in Fig. A.1.…”
Section: Appendix A: Continuum-subtraction Proceduresmentioning
confidence: 73%
See 2 more Smart Citations
“…), we obtain a separation of 114.2 ± 3.1 mas and a position angle of 136.9 ± 1.5 deg, which corresponds to a projected length of about 131 AU. This measurement and others collected in a time span of 26 yr (Koresko et al 1991;Haas et al 1993;Thiebaut et al 1995;Barth et al 1994;Millan-Gabet et al 2002;Bonnefoy et al 2016) are reported in Fig. A.1.…”
Section: Appendix A: Continuum-subtraction Proceduresmentioning
confidence: 73%
“…The two sources, located at a distance of 1150 pc (Herbst et al 1978), are separated by 0 . 1 and only recently high angular resolution observations with adaptive optics (AO) systems and interferometers have allowed the separatele determination of the properties of the two sources (Bonnefoy et al 2016;Hinkley et al 2013). The Herbig star, which is responsible for the variability of the binary (Bonnefoy et al 2016), has shown recurrent variations in the visual magnitude of 2−3 mag in the last ten years with recent major events recorded in , 2011(see light curves in Canovas et al 2012Maehara & Ukita 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the first outburst is in full agreement with typical EXor outbursts (e.g., Herbig et al 2001), the second one is unusual in length and in magnitude. The length of the 2014-2017 outburst is shorter than typical FUors, although several FUor outbursts lasting only a few years have been observed (e.g., ZCMa, V1647 Ori, [CTF93]216-2; Fedele et al 2007;Aspin 2011;Caratti o Garatti et al 2011;Audard et al 2014;Bonnefoy et al 2016). Objects with similar outburst lengths are often referred to as EXors, but this is typically accompanied by a question mark or considered as an intermediate case, especially if some FUor characteristics are present (e.g., Ábrahám et al 2004;Fedele et al 2007;Caratti o Garatti et al 2011).…”
Section: Discussion: the Variable Nature Of Asassn-13dbmentioning
confidence: 99%
“…We are concerned that the Gaia measurements in 2014-2016 might have suffered significantly from photometric variabilities of this binary system with a d = 0. 11 separation (Bonnefoy et al 2017). We therefore assume d=1000 pc based on Kaltcheva & Hilditch (2000).…”
Section: Facilities: Subaru (Hiciao)mentioning
confidence: 99%